Pharmacokinetic and Tissue Distributions of Naringenin and Naringenin Nanosuspension - Rajamani, Sumathi (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The purpose of this study was to investigate the pharmacokinetic properties and tissue biodistribution of naringenin nanosuspension (NAR-NS) with that of NAR solution (NAR-S) after oral administration. Materials and Methods: NAR is a major antioxidant flavonoid present in citrus fruits and herbs. It is an auspicious drug based on its good bioactivity, but the use of NAR is clinically hindered because of its poor solubility and bioavailability. Hence, it was formulated as a NS. A simple and rapid high-performance liquid chromatography method for the determination of NAR-S and NAR-NS present in plasma and tissue has been developed and validated. Biological samples were processed by simple protein precipitation. Results: NS formulation showed significantly improved solubility and oral bioavailability of NAR. Conclusion: Thus leads to a wider clinical application.